Continental-scale soil carbon composition and vulnerability modulated by regional environmental controls - Viscarra Rossel, Raphael; Lee, Juhwan; Behrens, T.; Luo, Z.; Baldock, J.; Richards, A. (NATURE PUBLISHING GROUP, 2019)
© 2019, The Author(s), under exclusive licence to Springer Nature Limited. Soil organic carbon (C) is an essential component of the global C cycle. Processes that control its composition and dynamics over large scales are not well understood. Thus, our understanding of C cycling is incomplete, which makes it difficult to predict C gains and losses due to changes in climate, land use and management. Here we show that controls on the composition of organic C, the particulate, humus and resistant fractions, and the potential vulnerability of C to decomposition across Australia are distinct, scale-dependent and variable. We used machine-learning with 5,721 topsoil measurements to show that, continentally, the climate, soil properties (for example, total nitrogen and pH) and elevation are dominant controls. However, we found that such general assessments disregard underlying region-specific controls that affect the distribution of the organic C fractions and vulnerability. This can lead to misinterpretations that prejudice our understanding of soil C processes and dynamics. Regionally, climate is mediated through interactions with soil properties, mineralogy and topography. In some regions, climate is uninfluential. These results highlight the need for regional assessments of soil C dynamics and more local parameterization of biogeochemical and Earth system models. Our analysis propounds the development of region-specific strategies for effective C management and climate change mitigation.